2021
DOI: 10.1021/acsami.0c21976
|View full text |Cite
|
Sign up to set email alerts
|

Piezocatalytic Effect Induced Hydrogen Production from Water over Non-noble Metal Ni Deposited Ultralong GaN Nanowires

Abstract: Piezoelectric material-based catalysis that relies on an external stress-induced piezopotential has been demonstrated to be an effective strategy toward various chemical reactions. In this work, non-noble metal Ni-decorated ultralong monocrystal GaN nanowires (NWs) were prepared through a chemical vapor deposition (CVD) technique, followed by a photodeposition method. The piezocatalytic activity of the GaN NWs was enhanced by ∼9 times after depositing the Ni cocatalyst, generating hydrogen gas of ∼88.3 μmol·g–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 73 publications
0
13
1
Order By: Relevance
“…The UiO-66 MOF presents a negligible H 2 production amount of merely about 5 μmol within 5 h. In contrast, the UiO-66-F 4 sample exhibits a significantly enhanced water splitting performance, with 178.5 μmol g −1 H 2 being produced under the same conditions, which is more than 100 times higher than that of the original UiO-66 host. The piezocatalytic H 2 production activity of UiO-66-F 4 is higher than that of previously reported organolead halide perovskite CH 3 NH 3 PbI 3 , 45 GaN nanowires, 12 and few-layer TMDs. 14 The piezocatalytic activity of the UiO-66-F 4 nanosheets was further evaluated under different frequencies of ultrasonication (Fig.…”
Section: Resultscontrasting
confidence: 61%
See 1 more Smart Citation
“…The UiO-66 MOF presents a negligible H 2 production amount of merely about 5 μmol within 5 h. In contrast, the UiO-66-F 4 sample exhibits a significantly enhanced water splitting performance, with 178.5 μmol g −1 H 2 being produced under the same conditions, which is more than 100 times higher than that of the original UiO-66 host. The piezocatalytic H 2 production activity of UiO-66-F 4 is higher than that of previously reported organolead halide perovskite CH 3 NH 3 PbI 3 , 45 GaN nanowires, 12 and few-layer TMDs. 14 The piezocatalytic activity of the UiO-66-F 4 nanosheets was further evaluated under different frequencies of ultrasonication (Fig.…”
Section: Resultscontrasting
confidence: 61%
“…, BaTiO 3 , 7 BiFeO 3 , 8 Bi 0.5 Na 0.5 TiO 3 9 and AgNbO 3 10 ), nitrides ( e.g. , C 3 N 4 11 and GaN 12 ), and transition metal dichalcogenides (TMDs). 13–15 .…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that surface properties of a catalyst particle play key roles in catalytic performance as a catalytic reaction always occurs on the surface of solid catalysts in heterogeneous catalysis . Surface modifications such as exposed facet engineering and surface decoration of nanoparticles (NPs) are effective approaches to enhance catalytic efficiency. It has been reported that different exposed facets may result in the accumulation of electrons or holes and thus facilitate the separation of charge carriers.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we found that the piezocatalytic activity of BTO nanocubes bound by {001} facets with selectively deposited Ag NPs on a positively polar end is around 2–5 times higher than that of pure BTO in the piezocatalytic degradation of different organic pollutants . However, in the research field of piezocatalysis, only a few works investigated the positive effect of individual surface-decorated cocatalysts on piezocatalytic efficiency. ,, Few works have been carried out to investigate the synergistic effect of “selective-facet-loaded electron and hole collectors” on piezocatalytic activity. Therefore, it can be meaningful and interesting to investigate the piezocatalytic activity of the modified piezocatalysts with rationally decorated cocatalysts on different facets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation